Stability of Ships and Other Bodies - Bar-Meir, Genick (Open textbook library., 2021)
This book, Stability of Ships and Other Bodies, describes the fundamentals when and why floating bodies are stable. In addition, it describes steps that transforms un–stable bodies to stable. This book is designed to replace all the other books and inseminate that recent developed technology and advances. The material in standard books is so entrenched, old, and outdated material that one can be only amazed. For example, concept like potential stability is not discussed or even mentioned in any of all the books that this author review. This book written from physical point of view rather then construction point of view like all the books review by this author on stability. It is hoped that the book could be used as a reference book for people who have at least some basics knowledge of science areas such as algebra, basic physics, etc. Even without deep understating the graphs in this book can be used to find necessarily quantities needed to understand if to fix your vessel.